ANALISIS STRATEGI PEMASARAN PADA UMKM DUPA JULUNGWANGI DALAM MENINGKATKAN PENJUALAN - Nuryani, Ni Nyoman Juli; Trisna Ayu Absari, Ni Kadek (Jurnal Daya Saing, 2025)
The research on the marketing strategy analysis of UKM Dupa Julungwangi aims to understand the marketing strategy of UKM Dupa Julungwangi in increasing its sales. It analyzes the strategies used by applying the marketing mix consisting of the 4P (Product,Price,Place,Promotion). This research uses a qualitative descriptive method because it aims to describe the conditions in the field. The data collection techniques used in this study are observation, interviews, and documentation. The data analysis techniques applied in this study are data reduction, data presentation, and conclusion drawing. Consumers are commonly referred to as the central point that must be considered by the market. UD Dupa Julungwangi is an MSME engaged in the retail sector, particularly incense and other worship supplies. In the production process of incense, UD Dupa Julungwangi has a very good development due to the curiosity strategy used, which can compete with other companies in the same field. This study uses qualitative research with the main informants being the owner of UD Dupa Julungwangi and several consumers/customers. The results of the study show that a good marketing strategy can increase product sales at UD Dupa Julungwangi. Thus, marketing strategy is very important to pay attention to in order to develop the company in the future.